Kamikate landslide: a case study of rainfall triggered landslide in far western Nepal - Dwivedi, SK; Ojha, G; Koirala, MP; Dwivedi, S (Journal of Nepal Geological Society, 2008)
The Kamikate landslide lies near Matena village of the Mahendranagar Municipality in far western Nepal. This landslide has been threat to local people and has caused shifting of the Kamikate Khola and erosion of fertile land downstream. Geologically, the area falls in the sub-Himalayan zone of far western Nepal. Landslide area is characterized by highly fractured and weathered alternating sedimentary beds of sandstone and mudstone. As the permeability of these rocks is high this causes large amount of precipitation to infiltrate. A detailed study of causes and mechanism of failure was carried out in the field. Based on the field assessment, recent satellite image study, arial photo investigation and safety factor analysis it reveals that the landslide is quite unstable in the monsoon period. Therefore, countermeasures plan such as gulley protection works; bio-engineering works which are urgently needed are discussed in the paper. Journal of Nepal Geological Society, 2007, Vol. 36 (Sp. Issue) p.22